Analisis Problematika Minat Baca Mahasantri Intensif Putri IDIA Prenduan - Fathorrohman Fathorrohman; Mariani Mariani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Female students are one of the human resources, which is needed in various aspects of life, one of which is the need for ideas and opinions to develop this country. The quality of current human resources is closely related to the interest in reading possessed by female students. Reading is not only related to the teaching and learning process, but is able to shape one's personality by living up to what he reads. The problem raised in this study is an analysis of the problematic reading interest of female intensive female students at the IDIA Prenduan campus which is described in two focuses, namely: 1. Why has there been a decrease in reading interest in Idia Prenduan female intensive student students 2. What are the impacts of the low interest in reading intensive female student IDIA Guide. To find out more about the problem of reading interest, the researcher used a qualitative field approach. The method used is the method of interviews, observation, and documentation. From this research, researchers process and analyze it to obtain data or information. The subjects of this study were female intensive female students and librarians. For the validity of the data, researchers used technical triangulation. From this method, research will process and analyze to obtain data or information. The subjects of this study were female intensive female students and librarians. For the validity of the data, researchers used the triangulation technique. The results showed that several factors were identified as the cause of the low interest in reading by IDIA Prenduan female intensive female students, including: the smooth use of electronic media by female students, the internal motivation of the children, the tight schedule on campus, and the low interest in reading female students. This impact causes low knowledge and insight, as well as several other diseases such as: creativity, communication and socialization skills and being unable to answer questions during exams and presentati.